Application of multimicroscopic techniques (LM and SEM) in comparative palynological study of Asteroideae members, inhabited in Pakistan. Issue 5 (17th December 2020) - Younis, Sidra; Shaheen, Shabnum; Harun, Nidaa; Abbas, Moneeza; Ahmad, Mushtaq; Hussain, Khadim; Khan, Farah
Abstract: In the present study light and scanning electron microscopic approaches were used to study the palynological variations among 30 Asteroideae members. Variety of qualitative and quantitative palynological characters like pollen shape and type, pollen sculpturing, pollen size, P/E ratio, exine and intine thickness, interspecific difference, colpi size, pore size, spines length, spine width, and pollen fertility were observed. Results reported remarkable variations among pollen characters of studied taxa. The shape of pollen grains in polar and equatorial views varied from specie to specie such as spheroidal, prolate, oblate, subspheroidal, oblate spheroidal, prolate spheroidal, suboblate, and sub prolate. Bidens pilosa L. showed maximum pollen size in both polar and equatorial views, whereas minimum pollen size in polar view was found in Tetraneuris scaposa (DC.) Greene. (i.e., 30.5 μm) and in equatorial view was found in Cosmos sulphureus Cav. (25.5 μm).The highest P/E ratio (1.39 μm) was measured in Glebionis coronaria L. The values of exine and intine thickness also varied. Tricolporate, tetracolporate, trizonocolporate, pentoporate, and polypentoporate pollen types were examined. Spinateand echinate pollen sculpturingobserved under SEM. Variations in spine length and width also recorded. The maximum pollen fertility (98%) was measured in Chrysanthemum morifolium Ramat. and the lowest (56%) was recorded in Thymophylla tenuiloba (DC.) Small. It was concluded that the variations in qualitative and quantitative characters were seemed to be valuable for the taxonomic investigations of Asteroideae taxa. Abstract : This study highlights the significance of light and scanning electron microscopy in the palynological characterization of Asteroideae members. A variety of palynological characters has been observed that can be worthwhile in the identification and delimitation of studied Asteroideae taxa.